1986
DOI: 10.1152/jappl.1986.60.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal-endocrine responses to head-out immersion at night

Abstract: Cardiorenal-endocrine responses to 3-h head-out immersion (HOI) (water temperature = 34.5 +/- 0.5 degrees C) were studied during day (0900-1400 h) and night (2300-0400 h) in six hydropenic male human subjects. Although HOI induced a reversible increase in urine flow in all subjects, the response was faster and greater in magnitude during the day compared with night (P less than 0.05). Na excretion and osmolal clearance (Cosm) also followed the identical response pattern as urine flow, and in fact, the HOI-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Shiraki et al [ 128] confirmed and extended the obser vations of Krishna and Donavitch [127], To assess whether the blunted nocturnal natriuresis might have been attributable to a lesser degree of central fluid trans location induced by immersion at night, they directly assessed the extent of the central hypervolemia induced by immersion at day and at night. Shiraki et al [128] studied 6 hydropenic male subjects during day and night immersion.…”
Section: Diurnal Variationmentioning
confidence: 86%
See 1 more Smart Citation
“…Shiraki et al [ 128] confirmed and extended the obser vations of Krishna and Donavitch [127], To assess whether the blunted nocturnal natriuresis might have been attributable to a lesser degree of central fluid trans location induced by immersion at night, they directly assessed the extent of the central hypervolemia induced by immersion at day and at night. Shiraki et al [128] studied 6 hydropenic male subjects during day and night immersion.…”
Section: Diurnal Variationmentioning
confidence: 86%
“…In humans, the urinary excretion of sodium and potassium show pronounced circadian rhythms with maximal rates in the early afternoon and minimal rates soon after midnight [124][125][126], Krishna and Danovitch [127] and Shiraki et al [128] have extended these observations and have clearly docu mented that immersion-induced diuresis and natriuresis are subject to a significant circadian variation. Thus, Krishna and Danovitch [127] carried out immersion studies in normal, sodium-replete subjects during the day (09.00-13.00 h) and during the night (00.00-04.00 h) in order to determine if the renal response to this natriuretic stimulus was influenced by the time of day.…”
Section: Diurnal Variationmentioning
confidence: 99%
“…It has been previously shown that the diuresis and natriuresis associated with either head-out immersion in water or in response to infusion of 2 liters of normal saline is reduced at night (2), but the difference between daytime and nighttime responses was almost entirely due to differences in osmotic (as opposed to free water) clearance (2,3). The mechanisms that lead to the difference in water handling have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding was accompanied by the lack of an AOH response; plasma-renin-angiotensin (PRA) and aldosterone responses remained normal. The dissociation of cardiorenal responses can be further demonstrated by the nocturnal attenuation of renal responses to WI ; cardiac responses are unaltered [27]. The lack of a tight coupling of the cardiac-renal-endocrine responses to WI strongly suggests that while the Gauer-Henry mechanisms may play an important role in eliciting renal-endocrine responses to WI, other mechanisms must contribute to the overall outcome.…”
Section: Weightlessness Acute Exposurementioning
confidence: 99%
“…The data from these experiments are presented in table III. The + 2 G z protocol was tolerated for [20][21][22][23][24][25][26][27][28] min, while + 3 G z was tolerated for only [12][13][14][15][16][17][18][19][20] min by which time the subjects developed narrowing peripheral vision. The subjects appeared to maintain their initial adaptations to + G z .…”
Section: Increased Gravitational Force (+ Gjmentioning
confidence: 99%